Visual Modeling of Controlled EMF Model Transformation using HENSHIN - Ermel, Claudia; Biermann, Enrico; Schmidt, Johann; Warning, Angeline (Electronic Communications of the EASST, 2011)
Abstract: The tool HENSHIN is an Eclipse plug-in supporting visual modeling and execution of rule-based EMF model transformations. This paper describes the recent extensions of HENSHIN by control structures for controlled rule applications. The control structures comprise well-known imperative structures like sequences and conditions on rule applications. Moreover, application conditions for individual rules may now be arbitrarily nested and combined by logical connectors. We present the extension of the visual EMF model transformation environment HENSHIN to edit and perform controlled EMF model transformations along an example modeling a reactive Web service-based application (personal mobility manager).